The seven wonders of the world: Wonders Of The East, Ghosts Of Wonder (Discovery Communications, 2010)
Wonders of the east and ghosts of wonder : the Hanging Gardens of Babylon, the Temple of Artemis at Ephesus, and the Pyramids of Egypt
Keywords: Seven Wonders of the World -- Curiosities and wonders -- Architecture, Ancient